Development and Evaluation of Grain Yield Monitoring System - Sharma, Karun; Singh, Manjeet; Singh, Bhupinder; Sharma, Ankit; Mishra, P K (Journal of Agricultural Engineering, 2013)
An yield monitor was developed by assembling the designed and selected components such as auxiliary tank, single point parallel type load cell, inductive proximity sensor and display unit with micro-controller on a combine harvester. It was evaluated on rice crop at two levels of monitoring (discrete and continuous), and three forward speeds (2.0, 3.0 and 4.5 km.h-1) of combine harvester. The mean value of measured yield was 4609.5 kg.ha-1 (s. d. of 2116.7 kg.ha-1 and c.v. of 45.3%) during discrete type of monitoring. With continuous type of monitoring, the mean value of yield was 5513.7 kg.ha-1 (s. d. of 3337.7 kg.ha-1 and c. v. of 60.6%). The lag time was observed to be 12.6, 13.1 and 12.4 s at forward speeds of 2.0, 3.0 and 4.5 km.h-1, respectively. Average error of 6.03% was observed in the measurement of yield by the yield monitor.